(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes information about the use of innovative technologies in the educational system, and the fact that they play a decisive role in educating young people to be creative and independent in all aspects, which determine their intellectual capabilities and their flourishing and development, and modern educational and innovative technologies. This article discusses best practices in the field, understanding of the approach to education, and specific features of modern teaching methods. Today, the interest and attention to the use of interactive methods, innovative technologies, pedagogical and information technologies in the educational process is increasing day by day, one of the reasons for this is that until now, traditional education If in lim students are taught to acquire only ready-made knowledge, modern technologies teach them to search for the acquired knowledge by themselves, to study and analyze independently, and even to draw their own conclusions. In this process, the teacher creates conditions for the development, formation, learning and upbringing of the individual, and at the same time performs the functions of management and guidance. In the process of education, the student becomes the main figure. Today, consistent reforms are being implemented in the education system in our country. This, in turn, places many demands on the teacher. After all, the teacher is the main executor of the educational reform. Today, knowledge about pedagogical innovation, integration, and technology is extremely important in increasing the effectiveness of education.